Serum soluble intercellular adhesion molecule-1 (sICAM-1): A novel potential biomarker in severe acne vulgaris - Amany Ibrahim Mustafa; Adel Ali Ebrahim; Waleed Abdel Lateef Abel Halim; Eman Fawzy; Ahmed Fathy Abdou (Wolters Kluwer Medknow Publications, 2022)
Background: Acne vulgaris (AV) is a chronic inflammatory disorder. Intercellular adhesion molecule-1 (ICAM-1) is a vital adhesion molecule mediating cellular adhesion during the inflammatory process. Aims and Objectives: To evaluate serum soluble intercellular adhesion molecule-1 (sICAM-1) level in AV patients as an attempt to elucidate its role in acne pathogenesis and to relate with studied clinical parameters. Materials and Methods: Serum sICAM-1 level was measured using ELISA technique in 60 patients and 60 controls. Results: Serum sICAM-1 level was significantly elevated in studied patients than controls (P < 0.001). Additionally, its level increased significantly with increased acne severity (P < 0.001) but not in patients with post acne scars (P > 0.05). Conclusion: Serum sICAM-1 could be a marker for acne etiopathogenesis. Furthermore, it might be considered as a predictor for disease severity.